Equipping School Counselors for Antiracist Healing Centered Groups: A Critical Examination of Preparation, Connected Curricula, Professional Practice and Oversight - Kara P Ieva; Jordon Beasley; Sam Steen (Teaching and Supervision in Counseling, 2021)
This paper highlights the potential for school counselors to promote antiracist practices and racial healing engagement utilizing small group counseling to ultimately eliminate inequities in schools. However, counselor educator programs, founded on middle to upper class white ideals, worldviews, and narrowly focused theoretical frameworks, currently function in ways that fail to equip future school counselors with the group facilitation knowledge, skills, and dispositions necessary for equitable practice in schools across the nation using case illustrations and a broad current literature review, the authors conceptualize the rationale for more competencies beyond group course assignment, clinical requirements (e.g., CACREP standards, 2016), practice, and supervision. Critical questions for counselor educators to reflect upon for group and connected curricula transformation are provided.
Keywords: group counseling; school counseling; counselor education; antiracist school counseling